Adapting Coastal Collection Methods for River Assessment to Increase Data on Global Plastic Pollution: Examples From India and Indonesia - Owens, Katharine A.; Kamil, Puspita I. (Frontiers in Environmental Science, 2020)
Marine debris often begins as litter or waste on land. Rivers play an important role in transporting this debris from communities to ocean systems, and yet we lack data on debris in freshwater systems. This work promotes eliminating the gap in knowledge between debris in marine and freshwater systems by sharing a consistent, replicable methodology that can be used to improve data on freshwater shoreline debris. Expansion in the application of this method globally can allow researchers to ground-truth estimates of the debris entering the world’s oceans. It also provides data on the litter degrading in the world’s riverine systems, an important ecological problem in its own right often sidelined in work on marine debris. Improved ground-truthing may also help scientists answer the missing plastics question: the disparity between input estimates and measurement in the world’s oceans. Cataloging the way debris moves through, or remains a part of, freshwater systems is imperative to addressing the global plastic waste problem.